EFFECT OF WINE WASTE USAGE AS FEED TO LOCAL RABBIT INTERNAL NON CARCASS - C. G. R., Atmaja; Sriyani, N. L. P.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
A research has been carried out to determine the effect of wine waste usage as feed to local male rabbit ( Lepus nigricollis ) internal non carcass for 16 weeks in Tejakula Village, Buleleng Regency. The animal used in this research were 18 local male rabbit age 5 – 6 weeks. The randomized block design with three treatments and six blocks as replicates. The treatments were fed ration without wine waste as control diets (P0), fed ration containing 5% wine waste (P1), and fed ration containing 10% wine waste (P2). The variables observed in this research were percentage of lungs, heart, liver, kidney, and digestive tract. The results showed that the rabbit fed ration containing wine waste until level 10% has not significant different (P>0,05) on internal non carcass of local male rabbit. Keyword : local male rabbit, wine waste, internal non carcass